SAT0560 Serious Infection Events in the Psoriasis Longitudinal Assessment and Registry Study: Current Status of Observations. (9th June 2015) - Kalb, R.; Fiorentino, D.; Lebwohl, M.; Leonardi, C.; Toole, J.; Poulin, Y.; Cohen, A.; Goyal, K.; Calabro, S.; Langholff, W.; Fakharzadeh, S.
Abstract : Objectives: To report the effect of psoriasis treatments on the risk of serious infections in pts in PSOLAR. Methods: PSOLAR is a multicenter, intercontinental, longitudinal, disease-based registry for adult pts with psoriasis, who are eligible to receive systemic therapy based on standards of clinical practice. Cumulative incidence rates of serious infections were reported across treatment cohorts of pts exposed to ustekinumab, infliximab, adalimumab, etanercept, other biologics (e.g., discontinued or experimental drugs), and non-biologic therapy (i.e. including and excluding MTX). Pts exposed to cyclosporine and those who were only exposed to a biologic before the start of registry were excluded. Multivariate analyses using Cox hazard regression methodology were used to identify predictors of time to first serious infection and therapies were compared to MTX alone. The overall registry population, as well as subpopulations of new users of biologics was evaluated. Results: Data were analyzed from 11466 pts with psoriasis exposed to a biologic agent or a non-biologic therapy reflecting 22311 pt-years. Demographic and baseline characteristics were generally comparable across cohorts, although the proportions of pts with prior significant infections, cardiovascular disease, and psoriatic arthritis were higher in the infliximab cohort. The cumulative incidence rate of serious infections was 1.45/100PY (n=323) across treatment cohorts, and rates were numerically higher in the infliximab, adalimumab, and other biologics cohorts (2.49, 1.97, and 3.01/100 PY, respectively) compared with the etanercept, ustekinumab, MTX, and non-biologics cohorts (excluding MTX) (1.47, 0.83, 1.28, and 1.05/100PY, respectively). Generally, the most commonly reported serious infections were pneumonia and cellulitis across cohorts. Increasing age, serious infection history, presence of diabetes, infliximab or adalimumab exposure, and current smoking were associated with increased risk for serious infection. In the subpopulation of new users of biologics, only adalimumab was found to be associated with risk of serious infection, while in the narrower subpopulation of bio-naive biologic new users, none of the biologics were found to be associated with serious infection. Conclusions: Results from PSOLAR suggest a higher risk of serious infections with adalimumab and infliximab in comparison with methotrexate; increased risk was not observed with ustekinumab or etanercept. Disclosure of Interest: R. Kalb Grant/research support from: Janssen Scientific Affairs, LLC, D. Fiorentino Grant/research support from: Janssen Scientific Affairs, LLC, M. Lebwohl Grant/research support from: Janssen Scientific Affairs, LLC, C. Leonardi Grant/research support from: Janssen Scientific Affairs, LLC, J. Toole Grant/research support from: Janssen Scientific Affairs, LLC, Y. Poulin Grant/research support from: Janssen Scientific Affairs, LLC, A. Cohen Grant/research support from: Janssen Scientific Affairs, LLC, K. Goyal Employee of: Janssen Scientific Affairs, LLC, S. Calabro Employee of: Janssen Scientific Affairs, LLC, W. Langholff Employee of: Janssen Scientific Affairs, LLC, S. Fakharzadeh Employee of: Janssen Scientific Affairs, LLC